Clinical Application of Inferior Alveolar Nerve Block Device for Safe and Secure IANB by Any Operator - Tomoyasu Noguchi; Kento Odaka; Ken-ichi Fukuda (Pain Research and Management)
The inferior alveolar nerve block (IANB) is an established technique with a success rate of 60–80%; however, large errors have been reported among operators. Some dentists do not prefer to use IANB because of the risk of complications. Nevertheless, it is a useful technique for pain control, and a secure IANB offers significant benefits to operators and patients. This case series study aimed to investigate the efficacy of the “IANB Device,” a nerve block guide for IANB, and the adverse events associated with its use in clinical practice. IANB was performed using the device on five patients who had undergone detailed computed tomography examination for chronic orofacial pain in the third division of the trigeminal nerve. Lidocaine 1% (1 mL, no adrenaline added) was used as the local anesthetic. IANB was performed by three dentists with 2, 5, and 11 years of experience in orofacial pain treatment. Thus, the data were collected in triplicate for each patient. The primary endpoints were whether adjustment of the IANB device was required, changes in the sensation threshold of the lower lip, the time to disappearance of pain, the presence or absence of tongue sensation (“Do you have numbness in your tongue?”: “Yes/No”), and discomfort (visual analog scale). The incidence of any other adverse events was recorded. The procedure was judged to be successful if the pain disappeared and an elevation in the sensation threshold of the lower lip was observed. Adjustment of the IANB device was not required in any patient. A significant elevation in the sensation threshold of the lower lip and the disappearance of pain were observed in all patients. Three of the five patients reported experiencing tongue numbness. Discomfort with the use of the IANB device was less than 30 mm on the visual analog scale. No notable complications were observed. The appropriate type, concentration, and dosage of the local anesthetic must be considered during general dental treatment and oral surgical procedures. Our findings suggest that the IANB device is useful for eliminating errors between operators, enhancing safety, and improving the success rate.